Improving the Management of Betawi Cultural Villages as Indonesian Cultural Sites - Winda Dwi Astuti Zebua; Fadhlan Arrasyid Hadizein; Lingga Syahid Ramadhan Ramadhan; Shubham Bapusaheb Wakchaure; Istisari Bulan Lageni (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The purpose of this community service is to provide a good intervention for the Betawi Cultural Village through sharing activities about SWOT from the area in order to find out what needs attention so that it not only attracts tourists to travel, but can also attract attention in the field of education to preserve the culture that exist and to help overcome problems by paying attention to needs so that they can function optimally. The method used in this program is to hold meetings in discussion forums to convey several inputs that need to be considered in improving the management of Setu Bakakan tourist attractions, one of which explains the importance of clarity of information and consistency in public communication. The results obtained after holding meetings and discussions regarding problems for improving Setu Babakan, one of which is the addition of foreign languages to the Setu Babakan website